Intrauterine fetal transfusion for red-cell alloimmunisation: a single-centre study over 15 years. (18th April 2012) - Walsh, CA; Russell, N; Carroll, S; Mahony, R; Higgins, S; McAuliffe, FM; McParland, P
Abstract : Objective: To examine perinatal outcomes following intrauterine fetal transfusion (IUT), in a single tertiary fetal medicine unit over a 15-year period. Study design: A retrospective analysis of women undergoing IUT in the National Maternity Hospital, Dublin from 1996-2010. Eligible cases were identified from a prospectively collated transfusion register. Cases of alloimmune thrombocytopenia, non-immune hydrops or parvovirus infection were excluded. The cord insertion was the preferred site, with the intra-hepatic vein and free cord reserved for inaccessible cases. All procedures were performed by 2 specialists in fetal medicine. Post-transfusion, women were admitted overnight, with biophysical profile and Doppler indices performed prior to discharge. Results: Between 1996 and 2010, 262 IUTs were performed in our unit, of which 244 (93%) were undertaken for red cell alloimmunisation, involving 97 pregnancies. The majority of women (84%) had anti-D antibodies, with a smaller incidence of anti-Kell (12%), anti-c (3%) and anti-E (1%) antibodies. Affected women underwent a median of 3 (IQR 2-4) procedures. In total, there were 3 intrauterine fetal deaths and 4 early neonatal deaths, for a perinatal mortality rate of 7%. The procedure-related loss rate was 1.2% (3/244). Two women had in utero fetal demise within 48 hours of the IUT, at 25 weeks and 29 weeks respectively. The third loss was from a cord haematoma at 32 weeks, with early neonatal demise. Conclusion: Intrauterine fetal transfusion is a safe procedure, associated with a low (1%) rate of procedure-related fetal loss, when performed by experienced practitioners in a national referral centre.